UJI EFEKTIFITAS FORMULA SPRAY DARI MINYAK ATSIRI HERBA KEMANGI (Ocimum Sanctum L ) SEBAGAI REPELLENT NYAMUK Aedes aegypti - Resmi Aini; Rina Widiastuti; Nuha Afra Nadhifa (Jurnal Ilmiah Manuntung, 2016)
Dengue fever is transmitted by the bite of Aedes aegypti mosquitoes infected with denguevirus. Preparations antinyamuk much use of harmful chemicals such as DEET (diethylmetatoluamide) and permethrin that can lead to pollution of the environment, leavingno residue and cause resistance to the drug. To determine the activity of essential oils from herbs basil (Ocimum Sanctum L) in the preparation of spray as a mosquito repellent and determine the effective concentrationof the spray.This type of research is True experiment with design Post Test Only Control Group Design. Repellent activity was observed by means of spray is sprayed on the back of the hand probandus, then tested on female mosquitoes with the introduction into the cage containing20 mosquitoes each treatment. Spray essential oils showed repellent activity of Aedes aegypti with a value of correlation r = 0.964 higher concentration of essential oils the fewer mosquitoes that land. Spray herbal essential oil of basil (Ocimum basilicum L) has a repellent activitycompared to the negative control. The effectiveness of the herb basil essential oil sprayobtainedat 74.131 ppm lC50 and lC90 of  775.711 ppm